2010
DOI: 10.1093/neuonc/noq044
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam enhances p53-mediated MGMT inhibition and sensitizes glioblastoma cells to temozolomide

Abstract: Antiepileptic drugs (AEDs) are frequently used to treat seizures in glioma patients. AEDs may have an unrecognized impact in modulating O(6)-methylguanine-DNA methyltransferase (MGMT), a DNA repair protein that has an important role in tumor cell resistance to alkylating agents. We report that levetiracetam (LEV) is the most potent MGMT inhibitor among several AEDs with diverse MGMT regulatory actions. In vitro, when used at concentrations within the human therapeutic range for seizure prophylaxis, LEV decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 25 publications
(33 reference statements)
1
107
0
7
Order By: Relevance
“…To date, a number of methods have been described to inhibit MGMT; however, their significance in clinical use for the purpose of overcoming temozolomide resistance is still limited or unknown [3,37,38]. Here, we have shown that the molecular pathway linking MEK to MGMT expression could offer novel and rational targets for MGMT inactivation, specifically MEK (by SL327) and MDM2 (by Nutlin-3).…”
Section: Resultsmentioning
confidence: 87%
“…To date, a number of methods have been described to inhibit MGMT; however, their significance in clinical use for the purpose of overcoming temozolomide resistance is still limited or unknown [3,37,38]. Here, we have shown that the molecular pathway linking MEK to MGMT expression could offer novel and rational targets for MGMT inactivation, specifically MEK (by SL327) and MDM2 (by Nutlin-3).…”
Section: Resultsmentioning
confidence: 87%
“…We have checked multiple phospho-p53 antibodies and have not found any change in the phosphorylation of p53 under the influence of BG. In our prior work 48 we have described a mechanism of p53-induced MGMT inhibition which did not rely on activation via phosphorylation. We have shown that restoration of specific p53 function (even in mutated p53 cell lines)…”
Section: Bg (mentioning
confidence: 99%
“…There is an inverse correlation between the levels of MGMT and p53 tumor suppressor protein (46), where wild-type p53 suppresses transcription of MGMT expression (47) by direct binding to the MGMT promoter (48). Unfortunately p53 is often inactivated or suppressed in cancers and restoration of p53 activity remains essential to the success of some treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Because overexpression of p53 may suppress MGMT, targeting p53 may render GBM more sensitive to TMZ. Levetiracetam is often used in GBM patients to manage seizures, but its use may further benefit patients by augmenting p53-mediated MGMT suppression [61].…”
Section: O6-benzylguaninementioning
confidence: 99%